CONCEPTUAL GUIDELINES OF NURSES SPECIALIZED IN REHABILITATION NURSING IN PORTUGUESE HOSPITALS - Maria Manuela Martins; Olga Ribeiro; João Ventura (Associação Portuguesa dos Enfermeiros de Reabilitação, 2018)
Objective: To identify the most consensual conceptions of nursing, individuals, health and environment among the nurses specialists in rehabilitation nursing. Method: A quantitative, descriptive-exploratory study was carried out in 36 hospital institutions, and 306 specialist nurses were involved in this research. As a tool for data collection, it was performed a self-completion questionnaire. Results: Although there are differences in the five regions of the country, the nursing, individuals, health and environment conceptions that nurses in rehabilitation nursing designate as fully in accordance with their practice are those of Afaf Meleis, Dorothea Orem, Callista Roy and Madeleine Leininger. Conclusion: The congruence observed in the results regarding the different conceptions shows the consistency of the conceptual guidelines of the participants. In this sense, the challenge is to consolidate the support of the professional practice of nurses who are specialists in rehabilitation nursing in the theoretical frameworks whose conceptions are considered fully in accordance with their practice.